Considerations for Developing Online Bereavement Support Groups. Issue 2 (2nd April 2020) - Gibson, Allison; Wladkowski, Stephanie P.; Wallace, Cara L.; Anderson, Keith A.
Abstract: The loss of a family member or friend can have profound psychological and physical implications, particularly for individuals without bereavement support services. Online support groups can be an effective means of extending services beyond the traditional modes of delivery. This is especially true for populations that include isolated individuals and those with limited support networks, limited transportation, challenging time commitments, or reside in communities with limited services available. The literature over the last 10 years was reviewed to discern the potential opportunities and challenges of providing online bereavement support group services. Discussed are challenges for recruitment of participants, availability of technology resources, addressing privacy and confidentiality issues, participants' knowledge of technical equipment, legal considerations, ethical considerations, accessibility, and other best practices. Diverse populations such as adolescents, older adults, and rural communities must be uniquely considered when using online support groups.